Input Dominance and Development of Home Language in Russian-German Bilinguals - Gagarina, Natalia; Klassert, Annegret (Frontiers in Communication, 2018)
Bilingual children experience a rapid shift in language preference and input dominance from L1 to L2 upon entering kindergarten when regular contact with L2 starts. Though this change in dominance affects further L1 development, little is known about how various factors shape this. The present study examines the combined influence of different background factors including not only chronological age, age of onset of L2 (L2 AoO), and gender, but also various L1 input measures on L1 receptive and expressive lexical and morphological (case and verb inflections) development in Russian-German bilingual children. For lexical skills, we found a general strong impact of chronological age, gender, and input factors but a differential impact of L2 AoO. Only expressive lexical skills were influenced by language dominance). Morphological development was influenced in the following way: chronological age and gender were most relevant for the acquisition of verb inflection, whereas age, L1 use in the nuclear family and L2 AoO affected the acquisition of case on nouns. This pattern explains the findings of the second series of analyses of longitudinal data, which showed that case is more vulnerable than verb inflection to language attrition – or, taking another perspective – to heritage Russian grammar restructuring.